Toby Cartwright - Bilious Emesis in a Neonate - Amy Holthouser (Association of American Medical Colleges, 2009)
Abstract Introduction This resource is a problem-based learning case for first-year medical students learning the anatomy and embryology of the gastrointestinal system. It highlights four important gastrointestinal malformations: (1) Hirschprung's disease, (2) midgut malrotation and volvulus, (3) duodenal atresia, and (4) ileo-jejunal atresia. These four malformations each have a different mechanism, highlighting different key points about the embryological development of the gastrointestinal tract. In addition, the case provides the clinical presentation for each of these malformations including associated conditions, malformed structures, and expected X-ray findings. Methods Prior to the case, a student interviews a standardized patient posing as the mother of an infant presenting with bilious emesis and dehydration. On case day, this student presents the clinical case to the group as a background to the discussion of these four causes of bilious emesis. Students research their malformation using assigned questions and present their findings to the group, along with a representative X-ray for the disorder discussed. At the conclusion of the case, seven unknown x-rays are presented to the group for discussion and diagnosis of the disorder in the film. Additional details regarding the implementation of this case in the small-group setting are provided in the facilitator. Results This case was very well-received by students. They evaluated the session highly, especially the use of X-rays (both known and unknown). Students also enjoyed the patient interview and oral presentation skills practice. Discussion The session was so effective that multiple-choice questions were developed from its content and administered on the embryology exam.